(untitled) (TEST Ticontre. Theory Text Translation, 2020)
Cesare Pavese’s internment period in Brancaleone Calabro left a significant imprint on his writing. In fact, Pavese explored his incomprehension of the ancestral and peasant world of Calabria already in Il carcere, which was published in 1948, but mostly written before his first novel Paesi tuoi (1941). Both works delved within Pavese’s autobiography and highlighted his liminal position between the secureness of the city and the call of an irrational feeling coming from what stayed outside the city limits. This essay reads Pavese through Lacanian theory and addresses the traumatic encounter with otherness that inspired his interest in ethnography and anthropology. Through the analysis of Pavese’s experience of the Lacanian Real, my paper will eventually investigate the difficulties of a writer in Italy during the 1930s. It will identify, behind the search for a balance between the attraction for pre-capitalist irrational and the influence of American consumerism, a more thorough desire of escaping from the radical experience of irrationality represented by fascism.